PERILAKU HOMOSEKSUAL: MENCARI AKAR PADA FAKTOR GENETIK - Misri Gozan (Postgraduate State Islamic Institute (IAIN) Metro, 2016)
The study based on literatures on this article presents data that is critical discourses of homosexuality and genetics. This article does not disclose the direction of Islam in terms of homosexuality because it is so obvious expressed in the Koran and explained by the righteous mufassir, muslim clerics and scholars. There is no strong data linking specific genetic factors with the emergence of homosexual behavior. Research conducted by the proponents of homosexual showed no single gene that govern human behavior which is a very complex phenomena. In other words, the genes do not determine behavior of homosexuality in particular. Expressed genes responsible for the nature of homosexuality is also interpreted as genes responsible for other mental problems. The experts further revealed that homosexual orientation is strongly affected by the events and stimuli experienced by either of the environment with a growing degree of openness to homosexual behavior as well as due to the availability of information, especially in cyberspace. Some chemicals are suspected of causing physical changes and influence on sexual orientation. Efforts of healing through action or medical intervention are not impossible. Some researches suggest that homosexual behavior is more aggressive than men hetersexual both in individual and family scale. The author sees the belief that genetic factors are the reason for accepting homosexual behavior has no strong scientific roots. Behavior of homosexuality thus can actually be, or should be, repaired and healed.